Re-writing History / Re-constructing Memory: Uses and Re-uses of Archival and Found Footage in Yervant Gianikian and Angela Ricci Lucchi’s Barbaric Land (Pays Barbare, 2013) - Mariana Martínez Bonilla (Cinergie, 2020)
In the realm of the moving image we can find several examples of a tendency to revisit the past in order to rewrite or reconstruct historical events. Following the ideas of Ariella Azoulay (2019, 2013) about the potential history as a way to imagine other possible histories and the role of the archival materials for the reconstruction of the narratives about the past, this article analyzes the ways in which Yervant Gianikian (1942) and Angela Ricci Lucchi (1942-2018), throughout their works, call into question the hegemonic narratives of history. I will focus in the analysis of their film Barbaric Land (Pays Barbare, France, 2013), in which the directors worked with archival footage from the 1920's and 1930's, related to the Italian colonization of Ethiopia. The text addresses how, by using montage as a theoretical and technological tool, the couple examine critically those documents and narratives to contrast the colonial politics of Mussolini with the shocking reality of the African territory and its inhabitants. Finally, the paper analyzes the manipulation processes of those materials and the ways in which they explore the Fascist ideology that produced the images of the so called “barbaric land” and its “primitive” inhabitants.